THE EMPATHY ON BASED CULTURE STUDENTS IN LAMPUNG - Noviana Diswantika; Abdullah Qurbi (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
Empathy is the cognitive and emotional activity of feeling what others feel from their point of view without losing one's identity. A person is expected to have optimal empathy as a social entity because it impacts the quality of life, both among others and the environment. The empathy that is not well developed can be detrimental to the social community, especially high school students. High school students are the most difficult stage in building a personality, so it can affect life in terms of life development. On the other hand, the philosophical values of Lampung's cultural subculture show an openness to diversity that supports the development of the importance of empathy. This article aims to measure student empathy at the high school level and in terms of the Lampung cultural subculture. The research method uses a quantitative approach with a survey research design. The study results indicate that the philosophy of the Lampung community influences the majority of high school students by showing a high level of empathy. The research results are expected to provide a new perspective on culture that must be preserved to maintain and increase the value of empathy for the people of Lampung.